Effectiveness of informational decision aids and a live donor financial assistance program on pursuit of live kidney transplants in African American hemodialysis patients - Boulware, L. Ebony (BMC Nephrol, 2018)
BACKGROUND: African Americans have persistently poor access to living donor kidney transplants (LDKT). We conducted a small randomized trial to provide preliminary evidence of the effect of informational decision support and donor financial assistance interventions on African American hemodialysis patients’ pursuit of LDKT. METHODS: Study participants were randomly assigned to receive (1) Usual Care; (2) the Providing Resources to Enhance African American Patients’ Readiness to Make Decisions about Kidney Disease (PREPARED); or (3) PREPARED plus a living kidney donor financial assistance program. Our primary outcome was patients’ actions to pursue LDKT (discussions with family, friends, or doctor; initiation or completion of the recipient LDKT medical evaluation; or identification of a donor). We also measured participants’ attitudes, concerns, and perceptions of interventions’ usefulness. RESULTS: Of 329 screened, 92 patients were eligible and randomized to Usual Care (n = 31), PREPARED (n = 30), or PREPARED plus financial assistance (n = 31). Most participants reported interventions helped their decision making about renal replacement treatments (62%). However there were no statistically significant improvements in LDKT actions among groups over 6 months. Further, no participants utilized the living donor financial assistance benefit. CONCLUSIONS: Findings suggest these interventions may need to be paired with personal support or navigation services to overcome key communication, logistical, and financial barriers to LDKT. TRIAL REGISTRATION: ClinicalTrials.gov [NCT01439516] [August 31, 2011].